Provider-initiated HIV testing for paediatric inpatients and their caretakers is feasible and acceptable - Wanyenze, Rhoda K.; Nawavvu, Cecilia; Ouma, Joseph; Namale, Alice; Colebunders, Robert; Kamya, Moses R. (Tropical Medicine & International Health, 2019)
Early diagnosis of HIV-infected children remains a major challenge in Africa. Children who are hospitalised represent an opportunity for HIV diagnosis and appropriate treatment. We introduced HIV Counselling and Testing (HCT) for hospitalised children and their caretakers in Mulago teaching hospital in Uganda to assess its feasibility. methods We analysed routine program data for children and caretakers who were tested between February 2005 and February 2008 to assess the proportion of children and caretakers who were HIV- infected. We also assessed the level of immune suppression (CD4 percentage) in a subset of HIV infected children tested between January 2007 and December 2007. results Caretakers agreed to HIV testing for 8990 (92.8%) of the 9687 children who were offered HIV testing. Among the caretakers, 89.8% agreed to be tested. At the time of hospitalization, 41.3% of the caretakers had previously tested for HIV. Although 313 parents (mothers and fathers) reported that they had previously tested HIV positive, only 113 (36.3%) of these had tested their children prior to hospitalization. Overall HIV prevalence among caretakers was 16.7%. HIV prevalence among children was 12.4%, highest on the nutrition ward (30.8%). Of those children who underwent CD4 counts, 56.4% had a CD4 percentage of <20%. conclusion HCT for hospitalized children and their caretakers identiﬁed a signiﬁcant number of HIV infected children and caretakers. More than half of the children had advanced HIV disease. More intensive efforts are needed to ensure earlier diagnosis and linkage to care for HIV infected children.
Keywords: Provider initiated HIV testing and counselling (PITC); Hospital; Children; HIV prevalence; Africa